The ternary system Hf–Re–Al at 1000 °C - Zinko, Liana; Nychyporuk, Galyna; Matselko, Oksana; Gladyshevskii, Roman (Physics and Chemistry of Solid State, 2023)
The interaction of the components in the Hf–Re–Al system was investigated by X-ray powder diffraction and scanning electron microscopy with energy-dispersive X-ray spectroscopy. The isothermal section of the phase diagram at 1000 °C was constructed in the full concentration range. A new ternary compound Hf5Re2Al2, isostructural with Ti5Ga4 (hP18, P63/mcm), and two extended solid solutions Hf(Re,Al)2 were found.